Kepatuhan Wajib Pajak Hotel Di Badan Pendapatan Daerah Kota Madiun (Studi Kasus Hotel Bintang Lokal) Tahun 2021-2023 - Salsabilla, Nadiva Arti; Sulistiyowati, Liliek Nur; Zahri, Rihan Mustafa (Universitas PGRI Madiun, 2024)
This study aims to determine the level of compliance of hotel taxpayers at the Madiun City Regional Revenue Agency. The method in this research used is qualitative with a descriptive approach, which aims to describe tax compliance in depth. The population and sample of this study were 33 hotel taxpayers in Madiun city. Data is collected through 1 interviews, observation and documentation to get an overview of taxpayer compliance. The results show that the level of compliance of hotel taxpayers in Madiun city varies, with some taxpayers showing high compliance, while others still face various obstacles in fulfilling their tax obligations. Factors that influence taxpayer compliance such as understanding of tax regulations, the tax system, and socialization provided by the Madiun City Regional Revenue Agency. Recommendations from this study include increasing socialization and education about the importance of tax compliance. Thus, it is expected to increase the level of tax compliance in hotels in Madiun City.